Caetetermes fontesi, a new nasutiform termite (Isoptera: Termitidae: Nasutitermitinae) from French Guiana - Scheffrahn, Rudolf H. (Zootaxa, 2022)
Caetetermes fontesi sp. nov. is described from soldiers, workers, and winged imagos collected in French Guiana. Soldiers of C. fontesi are distinguished from Caetetermes taquarussu Fontes 1981, until now a monotypic genus, by their larger size, deeper coloration, and shorter and thicker nasus. The imago of C. fontesi is larger and the enteric valve of the dimorphic C. fontesi workers have larger cushions with more and longer spines than C. taquarussu. Worker dimorphism for Neotropical nasutitermitinae is discussed.